ANALISA SIFAT FISIK DAN KANDUNGAN NUTRISI TEPUNG TALAS (Colocasia esculenta L.) PADA SUHU PENGERINGAN YANG BERBEDA - La Choviya Hawa; Laras Putri Wigati; Dina Wahyu Indriani (AGROINTEK, 2020)
Taro flour is one of dried products of taro (Colocasia esculenta L.). The characteristics of taro flour that low water content has an important role in determining the storage time. The presence of water in materials is influenced by internal factors of material, processing, moisture of storage and packaging materials. The water level reduction technique commonly used is by drying process, one of them is by using a tray dryer machine. The aim of the study was to analyze the physical properties, and nutritional content of taro flour produced from drying taro chips using a tray dryer machine at a drying temperature of 50°C, 60°C and 70°C with drying times 5, 6, and 7 hours. The physical parameters observed were water content, density and color, the nutritional parameters observed were protein, fat, ash, carbohydrates and crude fiber. The results of study showed that the water content ranged from 6.14 - 8.34%, density ranged from 0.45 - 0.57 kg/m3 and the lightness parameter values ranged from 69.9 - 72.0, with redness values between 12.2 - 12.8 and yellowness values between 11.5 - 13.1. The highest values of protein, fat and carbohydrate were 8.34%, 0.38% and 86.94%. The highest ash and crude fiber values were 3.84% and 2.99%.